2011
DOI: 10.3748/wjg.v17.i35.4031
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, lifestyle risk factors, and distal colon adenoma: A retrospective cohort study

Abstract: Our results suggest that high BMI may increase the risk of colorectal adenoma in Korean adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
2
12
1
2
Order By: Relevance
“…We think that M2-PK levels in diabetic patients should be interpreted more cautiously. Many studies indicate that type -2 diabetic patients have an increased risk for developing cancer (15,16,18,(23)(24)(25). We could not find a relation between diabetes mellitus and histopathological diagnosis.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…We think that M2-PK levels in diabetic patients should be interpreted more cautiously. Many studies indicate that type -2 diabetic patients have an increased risk for developing cancer (15,16,18,(23)(24)(25). We could not find a relation between diabetes mellitus and histopathological diagnosis.…”
Section: Discussioncontrasting
confidence: 75%
“…The relationship between obesity and carcinogenesis is well known (16,(18)(19)(20). Number and size of adenomas were found to correlate with visceral fat accumulation (21).…”
Section: Discussionmentioning
confidence: 98%
“…This was in agreement with many other studies concluded that, higher tumor M2PK levels were found in patients with higher BMI. 22,23,24 But Haug et al 25 found no relationship between fecal M2PK levels and BMI so they addressed that obesity has no role in pathogenesis of cancer colon. The type of food consumed may affect the pathogenesis of cancer colon as high percentage of cancer colon patients 76% consumed low fiber and high protein diet and the mean level of M2PK in those patients was high (9.36±2.72), however no one in control group consumed such diet and their mean level of M2PK was normal (2.03±0.89) and this difference of food habit had a statistically significant importance (p value=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to CRC, studies that have suggested an association between clinical manifestations of MS and colorectal adenoma have shown considerable heterogeneity [12-17]. Moreover, there are only few studies examining the association between the individual components of MS and colorectal adenoma in Korea [18]. Thus, in the present study, we focused on the association between individual components of MS and colorectal adenoma in a Korean population.…”
Section: Introductionmentioning
confidence: 99%